Theoretical perspectives on commercial informality: Analysis from the perspective of poverty in Latin America - Valencia Burgos, Luis Carlos; Ricardo Jiménez, Luly Stephany (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article researches and compares different positions on commercial informality in Latin America, where a detailed and analytical review of this phenomenon is made, which is defined as the set of unregulated commercial activities that in these countries go over the line of the institutional framework, generating a deterioration of the social, economic, political, and even human structure. These difficulties have their origin in a series of situations such as poverty, unemployment, displacement, migration, illiteracy, among others, which are important to know and analyze in order to generate real solutions to these profound difficulties.